The effectiveness of Kuching Matang Bus Transport Company Berhad as a public transport provider in Kuching / Sumardi Sungit - Sungit, Sumardi (2003)
The study examines the problems and the satisfaction of the respondent towards the effectiveness of Kuching Matang Bus Transport Company Berhad as a public transport provider in Kuching. For this study, a sample of 100 respondent of the study area, which is Matang area and Petra Jaya area has selected to fill in the questionnaire that we distribute. Our focus in this study were based on the services provided by bus company and also focus on the problem faced by the people whom the passengers of the Matang Bus. Majority of the respondent are age between 19 to 25 years old and mostly comes from Malay race. The popular passengers of this transport are from the students because they only earn not more than RM 500 income per month. Other than that, it also had found that buses in this area do not provide enough bus to the public and the time of bus departure took about more than 1 hour and the services that been provided are not satisfied the respondent. Besides that, the respondent also do not satisfied with the fare which been provided by Kuching Matang Bus Transport Company Berhad. It also is found that most of respondent prefer to use automatic machine rather than by using conductor bus because it is easier and it was an appropriate way to collect fare and reduce the human error. Also been analyze was the way to improve the services in the bus which is the bus must be installed with the air conditioned to give more comfort and satisfaction for the passengers.